2021
DOI: 10.7759/cureus.13457
|View full text |Cite
|
Sign up to set email alerts
|

The Endonasal Endoscopic Management of Cerebrospinal Fluid Rhinorrhea

Abstract: Introduction Cerebrospinal fluid (CSF) rhinorrhea is the result of a bony defect at the skull base with disruption of the arachnoid, dura mater, and sinonasal mucosa that leads to an active CSF leak and flow of clear fluid from the nose. The endoscopic repair of CSF leaks and skull defects have been used by an increasing number of surgeons and is the standard of care for repairing CSF leaks. Materials and methods We conducted a retrospective study of all cases of CSF leaks mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Por ejemplo, la reparación endoscópica de defectos de la base del cráneo, como las fístulas de LCR, se asocia a menor tasa de complicaciones que la resección endoscópica de tumores. [ 3 , 13 , 14 , 16 ] Con respecto a los tumores de la base del cráneo, las lesiones benignas a menudo requieren una resección quirúrgica menos agresiva y por lo tanto, es menos probable que provoquen complicaciones. [ 12 ] En nuestra cohorte registramos 26 complicaciones (21.66%) distribuidas en 24 pacientes y solo 2 fallecimientos durante la internación.…”
Section: Discussionunclassified
“…Por ejemplo, la reparación endoscópica de defectos de la base del cráneo, como las fístulas de LCR, se asocia a menor tasa de complicaciones que la resección endoscópica de tumores. [ 3 , 13 , 14 , 16 ] Con respecto a los tumores de la base del cráneo, las lesiones benignas a menudo requieren una resección quirúrgica menos agresiva y por lo tanto, es menos probable que provoquen complicaciones. [ 12 ] En nuestra cohorte registramos 26 complicaciones (21.66%) distribuidas en 24 pacientes y solo 2 fallecimientos durante la internación.…”
Section: Discussionunclassified
“…These rates are superior compared to the success rates of 86% in craniotomy and extracranial methods for the surgical repair of CSF leaks [ 37 ]. A review of recent studies published over the past 5 years showed a high success rate with zero or very minimal immediate postoperative complications ( Table 6 ) [ 8 , 30 , 31 , 32 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. The variable success rates of endoscopic repair most likely reflect the surgeons’ technical experience, the timing of management, and the nature of the leak (high-pressure versus low-pressure).…”
Section: Discussionmentioning
confidence: 99%
“…A history of a sinonasal or neurosurgical procedure, head trauma, meningitis, and intracranial or skull base tumors should raise the suspicion of CSF leak. 12…”
Section: Etiology Of Leakmentioning
confidence: 99%